Application of inertial sensors system for diagnosis of taekwon-do`s forms performance - a case study - Wasik, J.; Mosler, D.; Góra, T.; Ortenburger, D. (Archives of Budo, 2020)
Background and Study Aim: New technology brings new ways to assess performance in the forms in martial arts from biomechanical perspective. The aim of this study is knowledge about the usefulness of kinematic assessment in objective analysis of rhythm (patterned recurrence of movement in time), tempo (speed of motion) and dynamics of taekwondo techniques while performing certain form.